Requirement of Helix P2.2 and Nucleotide G1 for Positioning the Cleavage Site and Cofactor of the glmS Ribozyme - Klein, Daniel J. (2007)
The glmS ribozyme is a catalytic RNA that self-cleaves at its 5′-end in the presence of glucosamine-6-phosphate (GlcN6P). We present structures of the glmS ribozyme from Thermoanaerobacter tengcongensis that are bound with the cofactor GlcN6P or the inhibitor glucose-6-phosphate (Glc6P) at 1.7 Å and 2.2 Å resolution, respectively. The two structures are indistinguishable in the conformations of the small molecules and of the RNA. GlcN6P binding becomes apparent crystallographically when the pH is raised to 8.5, where the ribozyme conformation is identical to that observed previously at pH 5.5. A key structural feature of this ribozyme is a short duplex (P2.2) that is formed between sequences just 3′ of the cleavage site and within the core domain, and which introduces a pseudoknot into the active site. Mutagenesis indicates that P2.2 is required for activity in cis- and trans-acting forms of the ribozyme. P2.2 formation in a trans-acting ribozyme was exploited to demonstrate that N1 of the guanine at position 1 contributes to GlcN6P binding by interacting with the phosphate of the cofactor. At neutral pH, RNAs with adenine, 2-aminopurine, dimethyladenine or purine substitutions at position 1 cleave faster with glucosamine than with GlcN6P. This altered cofactor preference provides biochemical support for the orientation of the cofactor within the active site. Our results establish two features of the glmS ribozyme that are important for its activity: a sequence within the core domain that selects and positions the cleavage-site sequence, and a nucleobase at position 1 that helps position GlcN6P.